Laboratory evaluation of horizontal coefficient of consolidation, Ch of fibrous peat soil - Wong, Leong Sing (2005)
Encountered extensively in wetlands, fibrous peat is considered as problematic soil because it exhibits unusual compression behaviour. When a mass of fibrous peat soil with both vertical and horizontal drainage boundaries is subjected to a consolidation pressure, rate of excess pore water dissipation from the soil in the horizontal direction is higher than that in the vertical direction. The rates of excess pore water dissipation from the soil in the vertical and horizontal directions are measured by vertical and horizontal coefficient of consolidation (cv and ch) respectively. This project report presents laboratory findings on the consolidation behaviour of fibrous peat from Bahru village, Pontian, Johor with respect to one dimensional vertical and radial consolidation. Results from hydraulic consolidation tests indicate that the ch/cv ratio of the soil is greater than 1 when the soil is subjected to consolidation pressure of 50 kPa, 100 kPa, and 200 kPa. This implies that the utilization of horizontal drain maybe suitable for soil improvement to accelerate the settlement of fibrous peat soil.